1992
DOI: 10.1083/jcb.117.4.825
|View full text |Cite
|
Sign up to set email alerts
|

Expression of SV-40 T antigen in the small intestinal epithelium of transgenic mice results in proliferative changes in the crypt and reentry of villus-associated enterocytes into the cell cycle but has no apparent effect on cellular differentiation programs and does not cause neoplastic transformation

Abstract: Abstract. The mouse intestinal epithelium represents a unique mammalian system for examining the relationship between cell division, commitment, and differentiation. Proliferation and differentiation are rapid, perpetual, and spatially well-organized processes that occur along the crypt-to-villus axis and involve clearly defined cell lineages derived from a common multipotent stem cell located near the base of each crypt. Nucleotides -1178 to +28 of the rat intestinal fatty acid binding protein gene were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 78 publications
3
60
0
Order By: Relevance
“…For instance, expression of full length SV40 LT in postmitotic, villus-associated enterocytes causes them to reenter the cell cycle without an apparent e ect on their state of di erentiation (Hauft et al, 1992) and a similar phenomenon is observed upon expression of LT in secretory cells of the colon (Asa et al, 1996;Lopez et al, 1995), pancreas (Lopez et al, 1995), retinal (Penna et al, 1998) and smooth muscle cells (March et al, 1999;Herring et al, 1999). However, some exceptions have been noticed: in adult animals where brain cells were forced to express LT under the control of the FGF1 promoter, tumors were produced which lacked terminal di erentiation markers for astrocytes or neurons, but expressed high levels of markers for proliferating cells.…”
Section: How Does T Antigen Action On Cellular Targets Contribute To mentioning
confidence: 94%
See 1 more Smart Citation
“…For instance, expression of full length SV40 LT in postmitotic, villus-associated enterocytes causes them to reenter the cell cycle without an apparent e ect on their state of di erentiation (Hauft et al, 1992) and a similar phenomenon is observed upon expression of LT in secretory cells of the colon (Asa et al, 1996;Lopez et al, 1995), pancreas (Lopez et al, 1995), retinal (Penna et al, 1998) and smooth muscle cells (March et al, 1999;Herring et al, 1999). However, some exceptions have been noticed: in adult animals where brain cells were forced to express LT under the control of the FGF1 promoter, tumors were produced which lacked terminal di erentiation markers for astrocytes or neurons, but expressed high levels of markers for proliferating cells.…”
Section: How Does T Antigen Action On Cellular Targets Contribute To mentioning
confidence: 94%
“…For instance, SV40 T antigen has been expressed in several di erentiated cell subpopulations of the small intestine and, although all of them originate from common precursor stem cells, the consequences of this expression are extremely di erent. While hyperplasia and dysplasia of the small intestine result from the production of T antigen in enterocytic cells (Hauft et al, 1992;Kim et al, 1994), no apparent pathology is detected in the small bowel in transgenic mice expressing the T antigen in secretory cells (Asa et al, 1996;Lee et al, 1992, Lopez et al, 1995. Expression of T antigen in Paneth cells results in a loss of the mature cell type and leads to an ampli®cation of cells showing an intermediate morphology between Paneth and goblet cells (Garabedian et al, 1997).…”
Section: How Does T Antigen Action On Cellular Targets Contribute To mentioning
confidence: 99%
“…However, according to a recent study showing that crypts contain four to six stem cells (Barker et al, 2007), all of the stem Vil-Cre  LoxP-Tag mice developed multiple adenocarcinomas of the intestine and colon at an average age of 6 months showing for the first time that Tag is able to efficiently transform epithelial cells of the colon and intestine leading to adenocarcinoma. Development of colon carcinoma in previous studies was not successful, probably because the promoter was not active in the putative stem cell region (Hauft et al, 1992, Gum et al, 2001. This hypothesis is supported by a recent published study, in which a stem cell-specific loss of Apc resulted in progressively growing colon cancer, in contrast to the deletion of Apc in short-lived transitamplifying cells (Barker et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…One postulates that colon carcinoma derives from these stem cells, which remain anchored to the base of the crypt during the fast epithelial turnover and accumulate mutations by high proliferative activity. According to this, it is not surprising that previous attempts to induce transformation of the differentiated cell population by Tag were not successful (Hauft et al, 1992;Gum et al, 2001Gum et al, , 2004.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation